2016
DOI: 10.18805/lr.v0iof.11047
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in fatty acid composition of fenugreek(Trigonella foenum-graecum L.) seed oil

Abstract: An analysis has been carried out to explore the genetic variation in seventeen selected varieties of fenugreek. Sixteen fatty acids were identified in seed oil. Linoleic acid (18:2; n-6) and -Linolenic acid (18:3; n-3) were the major contributor found in the range of 26-43% in variety Lam Selection. The MUFA content varied from 3.50% in Azad Methi to 19.31 % in Hisar Madhvi. The ratio of n-6 to n-3 fatty acids indicated that fenugreek seed lipids are a good source of PUFA. PCA identified linolenic and oleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Estragole and trans-anethole compounds were found in the sample contents of F. vulgare, P. anisum herbal seeds and oils in our GC/MS analysis, which are thought to be responsible for the milk-enhancing effect with phytoestrogenic effect (4,6,(16)(17)(18). In addition, hexadecanoic acid and 9,12-octadecanoic acid methyl ester which is known to be present in black seed and 9,12-octadecanoic acid in fenugreek seeds were also found in the Brand D tea samples (14,15,19,20). The Brand D tea was stated to contain fenugreek, fennel, galega, dill, anise, nettle, ginger, caraway, mint, coconut, linden, chamomile, chasteberry, and lemon balm.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Estragole and trans-anethole compounds were found in the sample contents of F. vulgare, P. anisum herbal seeds and oils in our GC/MS analysis, which are thought to be responsible for the milk-enhancing effect with phytoestrogenic effect (4,6,(16)(17)(18). In addition, hexadecanoic acid and 9,12-octadecanoic acid methyl ester which is known to be present in black seed and 9,12-octadecanoic acid in fenugreek seeds were also found in the Brand D tea samples (14,15,19,20). The Brand D tea was stated to contain fenugreek, fennel, galega, dill, anise, nettle, ginger, caraway, mint, coconut, linden, chamomile, chasteberry, and lemon balm.…”
Section: Discussionmentioning
confidence: 76%
“…According to the GC/MS analysis of F. vulgare and P. anisum, we identified estragole and trans-anethole as phytoestrogens (1,6,(16)(17)(18). In addition, 9,12-octadecanoic acid methyl ester (19) in black seed plant, 9,12-octadecanoic acid in fenugreek seed (20), and herniarin compounds in the M. Chamomille plant (21) were identified. The Brand B tea sample contains sucrose, maltodextrin, okra extract, vitamin C, raspberry leaf extract, lemongrass extract, fennel extract, rooibos extract, fenugreek extract, goat psoriasis extract, fennel oil, and black cumin, as stated on the label.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research is available on profiling fatty acids in sainfoin (seed and vegetative tissue) (Tarasenko et al., 2015; Wijekoon et al., 2020), and further research is needed full characterization of the lipophilic fraction. The lipid fraction of fenugreek seeds revealed that oleic acid (C18:1), linoleic acid (C18:2), and α‐linolenic acid (C18:3) are the main fatty acids present, but myristic acid (C14:0), pentadecylic acid (C15:0), palmitic acid (C16:0), margaric acid (C17:0), stearic acid (C18:0), arachidic acid (C20:0), eicosenoic acid (C20:1), and behenic acid (C22:0) were present in lower quantities (Chatterjee, Variyar, & Sharma, 2010, Bienkowski, Zuk‐Golaszewska, Kaliniewicz, & Golaszewski, 2017; Rathore et al., 2017).…”
Section: Composition Analysis Of Sainfoin and Fenugreekmentioning
confidence: 99%
“…In a recent publication, Rathore et al (2017) analyzed genotypic variability in fenugreek varieties for seed oil fatty acid composition and observed good combination of n-6 and n-3 fatty acids and recommend for blending of fenugreek oil for obtaining good quality cooking oil. With this preliminary information, present study was undertaken to evaluate promising diverse genotypes from across India for yield, diosgenin content and other grain quality parameters under normal and limited moisture stress conditions.…”
Section: Introductionmentioning
confidence: 99%